Topography and forest composition affecting the variability in fire severity and post-fire regeneration occurring after a large fire in the Mediterranean basin - Broncano, M J; RETANA, J (INTERNATIONAL JOURNAL OF WILDLAND FIRE, 2004)
This study relates the spatial variability in tree regeneration generated by fire with topography and pre-fire vegetation composition, and analyses how the pattern of fire severities determines post-fire regeneration of the dominant tree species (Pinus halepensis and Quercus ilex) in a large fire that occurred in north-eastern Spain in summer 1994. At the fire level, the proportion of the different fire severities in the burned area was characteristic of large fires that burn with high severity. At the level of plot, the variability of fire severity in the study site depended on two topographic characteristics: elevation and aspect. Plots burned with high fire severity were distributed at higher altitude than less severely burned plots, which were mainly distributed in south- and east-facing slopes. Fire severity also increased with Q. ilex density in the stand. The mosaic of fire severities determined both plant mortality and seedling regeneration. Mortality of stems caused by fire was very high in both species, but many Q. ilex individuals resprouted after fire. Seedling regeneration of P. halepensis showed large differences among plots in the burned area, reflecting large spatial variability due to the elevation gradient, the variation in density of adult pine trees, and the spatial variability created by fire.
Keywords: mortality; post-fire regeneration; resprouting

Land use changes, natural regeneration patterns, and restoration practices after a large wildfire in NE Spain: Challenges for fire ecology and landscape restoration - ESPELTA, J M; Rodrigo, a; Habrouk, A; Meghelli, N; Ordonez, J L; RETANA, J (FIRE AND BIOLOGICAL PROCESSES, 2002)
Great wildfires have recently affected sub-Mediterranean areas of central Catalonia (NE Spain). The large extension of the burned areas, as well as the fact that non-fire-prone vegetation has been severely affected, lead to ponder over the natural regeneration patterns occurring, and over the best strategies to restore and manage the burned areas. In the present study, we review the land use changes and the natural regeneration patterns observed after the large wildfire that occurred in Bages-Bergueda in 1994. The fire resulted in: (i) the creation of new croplands and pastures in previously forested areas, (ii) the expansion of mixed oak (Quercus ilex and Q. cerrioides) coppices, (iii) the failure of natural regeneration of the dominant tree species (Pinus nigra), leading to the appearance of areas without any tree regeneration. In this context, we discuss the results of different experiments carried out to reforest P nigra stands and to ameliorate the structure of mixed oak coppices.
Keywords: land use changes; Mediterranean areas; natural regeneration; Spain; wildfires

Constraints and trade-offs in Mediterranean plant communities: The case of holm oak-Aleppo pine forests - Zavala, M A; ESPELTA, J M; RETANA, J (The Botanical Review, 2000)
In this paper we review those aspects that are relevant to the development of a mechanistic ecological theory to account for the structure and dynamics of Mediterranean forests, focus- ing our attention on mixed forests of holm oak (Quercus ilex L.), a shade-tolerant, slow- growing species that resprouts vigorously after disturbance, and Aleppo pine (Pinus halepen- sis M.), a fast-growing, nonresprouting, shade-intolerant species. The main objectives of this report are: to introduce some of the primary features of these forests, showing their structural complexity and historical peculiarities; to show that much of this complexity can be concep- tually reduced to two main factors of variation, soil-moisture gradients and a complex inter- action of historical management and disturbance regimes; and to contrast the unique features of Mediterranean systems with other communities that have inspired generalization in ecol- ogy. Plants in Mediterranean-climate regions must face several environmental constraints dur- ing their life cycle: water limitation, competition for light, and a complex set of disturbance regimes, mainly fire, herbivory, and human exploitation. The response of co-occurring spe- cies to a given set of environmental constraints depends on a combination of physiological and morphological traits. In holm oak-Aleppo pine forests, the lower limit of distribution along a soil-moisture gradient appears to be controlled by dry-season water stress on seedling performance, and the upper limit seems to be controlled by shade tolerance relative to com- petitors. The processes that generate and maintain these patterns are related to the responses of the two species to the water and light environments that result from interacting gradients of disturbance and resource availability. The dynamics of mixed holm oak-Aleppo pine forests may be represented along two major environmental axes: water availability and light intensity; namely, time since last disturbance. At the regional scale, the presence of holm oak and Aleppo pine is expected to be driven mainly by the precipitation regime, with the proportion of Aleppo pine in- creasing toward the driest border and with holm oak being the dominant species in areas with higher precipitation. Changes of dominance of holm oak and Aleppo pine also re- spond to water availability at the local scale. In this case, variations between species de- pend on different factors in a complex way, because reduced soil-moisture levels may re- sult either from low precipitation or from topography and edaphic features. The dynamics of holm oak-Aleppo pine forests are also determined by temporal changes in canopy clo- sure; that is, forest recovery after disturbance. In this case, the proportion of Aleppo pine would increase in recently disturbed stands (i.e., with high light intensity reaching the for- est floor), whereas regeneration of holm oak would be dominant under partially closed canopies. Theories of forest dynamics developed in humid regions may apply only poorly to Medi- terranean plant communities, where vegetation change is qualitatively or quantitatively dif- ferent. Thus, succession in temperate forests appears to be driven by differences in light availability and shade tolerance; but in Mediterranean plant communities, water limitation is of greater importance for the distribution of forest species. In Mediterranean landscapes the interaction of life-history strategies with changing environments is difficult to infer from observational and experimental studies. A mechanistic approach, in which competi- tion or plant performance is measured as a function of resource availability, seems more feasible. The idea should be to develop multispeeies models calibrated specifically for Mediterranean forests in a combined program of modeling, field research, and experimenta- tion.
Keywords: Aleppo pine; disturbance regimes; forest dynamics; holm oak (voyant); light intensity; mediterranean plant-communities; Water availability

Supervivencia y crecimiento de plántulas de encina en función de la intensidad de luz y la disponibilidad de agua - J.Ma, ESPELTA; RETANA, J; Riba, M (II Congreso Forestal Español, 1997)
The response of holm oak seedlings under a gradient of light and water av ail abilit y is analyzed. Seedling survival under all water levels decreased with increasing light. Conceming seedling morphology, both light and water availability changed biomass allocation to roots, stems and leaves, being light the most important source of variation
Keywords: Holm oak; light; Regeneration; Seedling; water

Effect of site quality and thinning management on the structure of holm oak forests in northeast Spain - Gracia, M; RETANA, J (Ann. For. Sci., 1996)
In the holm oak forests of NE Spain, the variability of thinning intensity, together with the great heterogeneity of site quality, due to the rough topography of the region, gives rise to important structural differences among stands. In this paper, we analyze the effect of site quality and thinning management on the structural heterogeneity of holm oak stands at the end of the cutting cycle in different areas of the Montseny and Les Guilleries massifs (NE Spain). These two factors influence the main structural variables of the stands in various ways. Height was used as an indicator of site quality, because it was relatively unaffected by thinning management, while density and total number of stems per stool were strongly affected. Mean tree diameter reflected the effect of both site quality and thinning. The type of forest management was found to be the most important factor determining forest structure. Site quality was a constraint of stand development, contributing in poor stands, to increased differences due to thinning management.
Keywords: Forest structure; Holm oak; Ouercus ilex; site quality; thinning

SUPERVIVENCIA DE PLANTULAS DE PINO CARRASCA (PINUS HALEPENSIS) y ENCINA (QUERCUS ILEX) EN BOSQUE MIXTOS DE AMBAS ESPECIES - ESPELTA, J M; RETANA, J; Gené, C; Riba, M (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
In this paper, survival of holm oak and Aleppo pine seedlings in holm oak stands, Aleppo pine stands and mixed stands, both in cut and uncut plots, is analized. Survival of holm oak seedlings in uncut plots is greater than that of Aleppo pine seedlings in the three types of forest considered. Mortality of seedlings of both species in 9ut plots is considerably smaller than that of uncut plots. K.W.:
Keywords: Aleppo pine; Holm oak; mixed forest; Seedling; survival curve